Optimalisasi Pemilihan Title untuk Senjata pada Game Point Blank Menggunakan Metode TOPSIS - Koto, Derry Herlan; Dafitri, Haida (JiTEKH, 2024)
One of the main features in the point blank game is the title system, the benefit of the title gives the effect of the character gaining additional abilities and increased performance when using weapons. The purpose of this study is to create a website-based decision support system that can help point blank game players in choosing the optimal title combination for weapons, then a decision support system test is carried out using a data sample which will later be compared with the results of the manual calculation of the data sample, to obtain this purpose the method used in this study is the TOPSIS. The TOPSIS method is used because it is one of the methods in multi-criteria decision-making, which is known for its ease in calculating and interpreting results. Based on the results of the TOPSIS method calculation trial using a sample of 8 alternative and 7 criteria data, which were calculated manually and using the decision support system of this study, both produced title still assassin with a prevalence value of 0.36, title nimble sneaker with a prevalence value of 0.36, and title shooting star with a prevalence value of 0.325 are the recommendations of the results of this study for the combination of titles which fills 3 title slots in Game Point Blank for the use of assault rifles, sub machine guns, snipers, and shotguns.